Intégration mondiale de la Tunisie : (World Bank, 2008)
Doing Business 2009 is the sixth in a series of annual reports comparing business regulations in 181 countries, measuring regulations affecting 10 areas of everyday business: starting a business dealing with licenses employing workers registering property getting credit protecting investors paying taxes trading across borders enforcing contracts closing a business The 2009 edition of Doing Business updates all sets of indicators, ranks countries on their overall ease of doing business, and analyzes reforms to business regulation by identifying which countries are improving their business environment the most and which ones needs improvement. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why, focusing on how complex business regulations dampen investment, growth and job creation in all businesses, and especially opportunities for women entrepreneurs.